Computational Intelligence : International Joint Conference, IJCCI 2015 Lisbon, Portugal, November 12-14, 2015, Revised selected papers /: International Joint Conference, IJCCI 2015 Lisbon, Portugal, November 12-14, 2015, Revised selected papers. ([2017]) - Unknown
No abstract available